2016
DOI: 10.1016/j.mce.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of thyroid cancer: A 2015 update

Abstract: Thyroid cancer is the most common endocrine neoplasm, and its rate is rising at an alarming pace. Thus, there is a compelling need to develop in vivo models which will not only enable the confirmation of the oncogenic potential of driver genes, but also point the way towards the development of new therapeutics. Over the past 20 years, techniques for the generation of mouse models of human diseases have progressed substantially, accompanied by parallel advances in the genetics and genomics of human tumors. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 100 publications
(135 reference statements)
0
24
0
2
Order By: Relevance
“…The lack of successful treatment options for advanced thyroid cancer underscores the need for novel therapeutic strategies, as well as in vivo models that can help predict their clinical utility. In the past, in vivo models were developed by injecting human thyroid cancer cell lines into immunodeficient mouse strains . Immunodeficient models, however, fail to mimic the natural tumor microenvironment, because they do not evoke protective immune responses or tumor‐promoting inflammation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of successful treatment options for advanced thyroid cancer underscores the need for novel therapeutic strategies, as well as in vivo models that can help predict their clinical utility. In the past, in vivo models were developed by injecting human thyroid cancer cell lines into immunodeficient mouse strains . Immunodeficient models, however, fail to mimic the natural tumor microenvironment, because they do not evoke protective immune responses or tumor‐promoting inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Immunodeficient models, however, fail to mimic the natural tumor microenvironment, because they do not evoke protective immune responses or tumor‐promoting inflammation . For this reason, genetically engineered strains have been developed to study tumors that arise in situ in immunocompetent hosts . In order to rapidly induce tumor development, orthotopic injection of tumor cell lines derived from genetically engineered mice have also been used .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 44% of patients receiving a therapeutic dose of virus experienced 24:12 a reduction in tumor size. Preclinical studies to support more human trials would benefit from exploring OVs in orthotopic, immunocompetent murine models of thyroid cancer (Vanden Borre et al 2014, Kirschner et al 2016.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%
“…These models were generated by overexpressing mutated oncogenic RET or other oncogenes in transgenic mice or through the loss of tumour suppressor genes (Cote et al 2015, Kirschner et al 2016, Wiedemann & Pellegata 2016.…”
Section: Murine Modelsmentioning
confidence: 99%
“…Loss or mutations of these genes have been reported in many types of human cancers. It was found that mice bearing a single Rb mutant allele (Rb +/− ) develop pituitary tumours with almost complete penetrance (Cote et al 2015, Kirschner et al 2016. Rb +/− mice were also predisposed to develop C-cell hyperplasia, which subsequently progressed into MTC.…”
Section: Mouse Models With Mutations In Cell-cycle Control Genesmentioning
confidence: 99%